The emerging role of virtual reality training in rehabilitation - Ayesha Afridi; Arshad Nawaz Malik; Hina Tariq; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2022)
Virtual reality (VR) uses computer-generated simulations to create a virtual environment for users which appears, sounds, and feels like real-life objects and events. The use of VR in rehabilitation is relatively new and has demonstrated to be an effective tool in achieving desired clinical outcomes by active engagement of participants. Over the past few years, the use of VR in rehabilitation has rapidly increased because of its advantages over traditional rehabilitation techniques. These include better patient adherence to the rehabilitation protocols with high levels of engagement and motivation. This review summarises the available evidence on the role of VR in rehabilitation, its effects, and scope across different clinical conditions and outcomes. We also describe the current status of VR utilization in rehabilitation settings across Pakistan and highlight the need for further research. Keywords: Virtual reality, exergaming, augmented reality, narrative review, neurorehabilitation, advances.